2024
DOI: 10.1088/1752-7163/ad3fdf
|View full text |Cite
|
Sign up to set email alerts
|

Establishing breath as a biomarker platform—take home messages from the Breath Biopsy Conference 2023

Hsuan Chou,
Lucy Godbeer,
Madeleine L Ball

Abstract: The annual Breath Biopsy Conference hosted by Owlstone Medical gathers together the leading experts, early career researchers, and physicians working with breath as a biomarker platform for clinical purposes. The current topics in breath research are discussed and presented, and an overarching topical theme is identified and discussed as part of an expert panel to close the conference. The profiling of normal breath composition and the establishment of standards for analyzing breath compared to background sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This approach has been used during the development of the VOC Atlas, an ongoing project to develop a reference range of VOCs present in the breath that are able to be distinguished from background based on tiers of quantitative metrics (Hatch et al, n.d.). Due to how important this is to advance breath research, many groups both academic and industrial are also developing reference databases of normal human breath (Chou et al, 2024b ; Human Breath Atlas, 2024 ). Several reference databases from multiple sources and groups across the world and global collaboration in these efforts will allow for comparison between databases for even greater confidence in what the normal ranges of VOCs in the breath are.…”
Section: Breath Analysis Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…This approach has been used during the development of the VOC Atlas, an ongoing project to develop a reference range of VOCs present in the breath that are able to be distinguished from background based on tiers of quantitative metrics (Hatch et al, n.d.). Due to how important this is to advance breath research, many groups both academic and industrial are also developing reference databases of normal human breath (Chou et al, 2024b ; Human Breath Atlas, 2024 ). Several reference databases from multiple sources and groups across the world and global collaboration in these efforts will allow for comparison between databases for even greater confidence in what the normal ranges of VOCs in the breath are.…”
Section: Breath Analysis Methodologymentioning
confidence: 99%
“…Improving confidence in chemical identification has been a focal point for standardization in breath research, as highlighted by experts during previous breath conferences (Beauchamp et al, 2016 ; Chou et al, 2024a , 2024b ; Schmidt et al, 2021 ). Untargeted breath biomarker discovery workflows make up most breath VOC studies and often result in a list of tentatively identified VOCs through comparison to publicly available standard libraries, such as those provided by the National Institute of Standards and Technology (NIST).…”
Section: Developing Highly Sensitive and Specific Voc Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations